The office. Season two [videorecording (DVD)] - Daniels, Greg; Carell, Steve, 1962-; Wilson, Rainn, 1966-; Krasinski, John, 1979-; Fischer, Jenna, 1974- (Universal Studios Home Entertainment, 2006)
Documents the exploits of a paper supply company in Scranton, Pennsylvania. Made up of manager Michael Scott, a deluded boss who cares about the welfare of his employees while trying to put his own spin on company policy. From sexual politics to performance reviews to email espionage, the employees at Dunder-Mifflin are there to get the job done ... or not.